Quantum-Resistant Cryptography for Smart Metering in Smart Grid Systems - Janusz Jabłoński; Robert Dylewski (Energies)
The article proposes a cryptographic system with absolute security features for use in authenticating access to resources in smart grid systems, taking into account prosumer solutions to ensure a high level of security of transactions on the energy market that meet the requirements established in the Directive of the European Parliament of 14 December 2022 no. 2555 NIS2, requiring “dynamic authentication” prior to the release of transaction data for key services, covers energy market operators as a key service and is particularly important for ensuring security. The article presents an innovative cryptographic system that, according to the authors’ knowledge, is the only one in the world that meets the NIS2 requirements in the field of “dynamic authentication” and the Quantum-Resistant requirements intended for distributed systems and smart grids. The proposed solution eliminates vulnerabilities related to digital identity theft and its reuse, i.e., practically eliminates the possibility of impersonation.